تأثير جائحة كورونا على بيئة الأعمال في الجزائر - هيفاء شرايطية; أحلام حزايمية (My University, 2022)
This study aims to learn about the impact of the business environment on Algeria's economic institutions before and during the COVID-19 pandemic between 2017 and 2019 by drawing on the most important international indicators: the competitiveness index, the economic freedom index, the ease of doing business index. Through it, we have reached the following conclusions: To keep abreast of developments in Algeria's economic institutions during the coronavirus crisis, and benefit the business sector in Algeria, the business environment in Algeria is suffering through international indicators in the period 2017-2021, especially during the coronavirus crisis (2019-2021), from several crises that made it unsupportive for economic institutions and in a stable state. The coronavirus pandemic has led to a halt in most economic activities, especially the energy sector, whose incomes have halved as Algeria's main resource and the growth of GDP to 5.2%. high unemployment rates and high budget deficits, and the coronavirus pandemic has had a negative impact on all segments of society; And the fragile layer especially; Sudden cessation of economic movement and widespread unemployment. Although most of the repercussions of Covid-19 have been negative for Algeria's business environment However, combating, trapping and preventing the spread of HIV is much more important than potential economic and social repercussions. Preserving human beings as social capital is the foundation, and the impact of the coronavirus pandemic on Algeria has been particularly severe because of inadequate infrastructure. Although most of the negative economic repercussions were due to precautionary measures and measures, combating the COVID-19 virus and preventing its spread are much more important than potential economic repercussions. ............................................................. تهدف هذه الدراسة إلى معرفة واقع تأثير بيئة الأعمال على المؤسسات الاقتصادية في الجزائر قبل و أثناء ( بالاعتماد على أهم المؤشرات الدولية - جائحة كورونا )كوفيد المتمثلة في: مؤشر التنافسية، مؤشر الحرية الاقتصادية، مؤشر سهولة الأعمال، وقد اعتمدنا على التقا رير التالية، صندوق النقد العربي، البنك الدولي الجزائري، الديوان الوطني للإحصاء، قياس أنشطة ممارسة الأعمال. ومن خلالهاا توصلنا الى النتائج التالية: مواكبة التطورات التي تحصل في المؤسسات الاقتصادية الجزائرية أثناء ازمة كورونا ، وتفيد قطاع الأعمال في إن جائحة كورونا أسفرت عن أثار سلبية تسببت في توقف و تراجع معظم الانشطة الاقتصادية، خاصة قطاع الطاقة الذي تراجعت مداخيله إلى النصف باعتباره المورد الرئيسي للجزائر، كما تراجع النمو المحلي الإجمالي إلى 5.7 %؛ وارتفاع معدلات البطالة و ارتفاع عجز الميزانية ، وأثرت جائحة كورونا تأثيرا سلبا على فئات المجتمع كافة ؛ و الطبقة الهشة خاصة ؛مع التوقف المفاجئ للحركة الاقتصادية وانتشار البطالة. بالرغم من أن معظم تداعيات )كوفيد ( كانت سلبية على بيئة الأعمال الجزائرية، إلا أن مكافحة الفيروس و محاصرته و منع انتشاره ألم بكثير من التداعيات الاقتصادية و الاجتماعية المحتملة ، فالحفاظ على الإنسان كون رأس المال الاجتماعي هو الأساس، كما كان تأثير جائحة كورونا شديد بشكل خاص على الجزائر بسبب عدم كفاية البنية التحتية، إلى جانب الإفراط في الاعتماد على قطاع المحروقات، وعلى الرغم من أن معظم التداعيات الاقتصادية السلبية كانت بسبب الإجراءات والتدابير الاحترازية إلا أن مكافحة فيروس كوفيد ومنع انتشاره هو أهىم بكثير من التداعيات الاقتصادية المحتملة ، فالحفاظ على الإنسان كونه رأس مال الاجتماعي هو الاساس